SISTEM INFORMASI PSIKOTES ONLINE PADA PERUSAHAAN XYZ - Vadlya Maarif Vadlya; Hidayat Muhammad Nur; Mustofa Mustofa; Ahmad Nouvel; Sunanto Sunanto (Informatics and Computer Engineering Journal, 2023)
Companies that are engaged in the Control Process Instrumentation sector which requires HR (Human Resources) competent in their respective fields with the Recruitment section of the Human Resources Division to recruit qualified candidates in accordance with the criteria determined by the Prospective Employee Division. will work later. Each individual certainly has a different character and personality and each part of the company requires employees who have character according to work assignments. Therefore, companies need to conduct psychological tests to obtain data related to information on a prospective employee in the context of work. Currently, testing is done manually, which is very inefficient and time-consuming. Using CBT (Computer Base Test) is certainly a good solution because with computerization, starting from the test process to analyzing test data, it is easier and more effective to do. By answering questions online, of course there is no distance limit, prospective employees who want to practice without having to come directly to the head office are located. Also, the process that previously used the sheet method was difficult in storing archives, by using computerization all recorded data from each prospective employee could be centralized and easier to manage.